PENGARUH DIMENSI BANKING SERVICE QUALITY (BSQ) TERHADAP KEPUASAN NASABAH BANK - Sri Sumardiningsih; Wawan Sundawan; Lies Endarwati; Arif Wibowo; Yulia Ayriza (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2012)
Abstract: Effect of Banking Service Quality (BSQ) Dimensions towards Bank Customer Satisfaction. This study aims to determine the effect of Banking Service Quality (BSQ) to the customer satisfaction of BPD Bank in DIY. This research is a survey research with a sample of 1.536 respondents. The sample was taken by purposive sampling technique. Data collection instrument was questionnaires and analyzed using multiple regression. The results showed that six dimensions of BSQ simultaneously gave positive and significant impact on customer satisfaction. If seen from each dimension individually; the highest influence came from the reliability dimension and the lowest dimensions were from Access and Services Portfolio dimensions. For the national servants (PNS) customers, the BSQ six dimensions simultaneously gave a positive and significant impact on customer satisfaction; the highest influence came from the reliability dimension and the lowest was from portfolio services dimension. For the non national servants, the BSQ six dimensions simultaneously gave a positive and significant impact on customer satisfaction; the highest influence came from the reliability dimension and the lowest was from portfolio services dimension. Keywords: Banking Service Quality, Customer Satisfaction Abstrak: Pengaruh Dimensi Banking Service Quality (BSQ) Terhadap Kepuasan Nasabah Bank. Penelitian ini bertujuan untuk mengetahui pengaruh Banking Service Quality (BSQ) terhadap kepuasan nasabah Bank BPD di DIY. Penelitian ini merupakan penelitian survey dengan sampel secara keseluruhan berjumlah 1.536 responden. Sampel diambil dengan teknik purposive sampling. Instrumen pengumpulan data berupa kuesioner dan dianalisis dengan regresi ganda. Hasil penelitian menunjukkan keenam dimensi BSQ secara simultan berpengaruh positif dan signifikan terhadap kepuasan nasabah, jika dilihat tiap dimensi maka pengaruh tertinggi berasal dari dimensi keterhandalan dan terendah dari dimensi Akses serta Portofolio Jasa. Untuk nasabah PNS, keenam dimensi BSQ secara simultan berpengaruh positif dan signifikan terhadap kepuasan nasabah, pengaruh tertinggi berasal dari dimensi keterhandalan dan terendah berasal dari dimensi portofolio jasa, dan untuk nasabah non PNS, keenam dimensi BSQ secara simultan berpengaruh positif dan signifikan terhadap kepuasan nasabah, pengaruh tertinggi berasal dari dimensi keterhandalan dan terendah berasal dari dimensi portofolio jasa. Kata Kunci: Banking Service Quality, Kepuasan Nasabah